Analysis of Passenger Transport Mode Choice Between Bus and Airplane to Improve Service (Case Study: Palembang-Jakarta Route) - Renita Vira Maulidina; Sutanto Soehodho; Nahry Nahry (Transpublika Publisher, 2026)
The development of public transport in Indonesia is an important factor in supporting community mobility, especially in inter-city travel. This study aims to analyze the factors that influence the choice of transport mode between buses and airplanes on the Palembang-Jakarta route. This study uses the binary logistic regression method to identify the probability of users choosing one mode of transport based on various factors. Inter-city mobility in Indonesia is increasing, especially for travel between Palembang and Jakarta. The choice of efficient modes of transport is an important factor for users, with two main modes available, namely buses and airplanes. This study aims to analyze the factors that influence the choice of transportation mode by considering variables such as travel costs, travel time, comfort, safety, and accessibility. The research method used is binary logistic regression, which allows for the analysis of the probability of mode selection based on influential factors. Data was collected through a questionnaire survey involving respondents who had travelled from Palembang to Jakarta. Based on the results of the study, optimization of public transport services is needed to improve competitiveness and enhance travel comfort and safety. This study provides insights for transport service providers and policymakers in designing more efficient and sustainable transport policies.